Effectiveness of a cough management algorithm at the transitional phase from acute to chronic cough in Australian children aged <15 years: protocol for a randomised controlled trial. Issue 3 (3rd March 2017) - O'Grady, Kerry-Ann F; Grimwood, Keith; Toombs, Maree; Sloots, Theo P; Otim, Michael; Whiley, David; Anderson, Jennie; Rablin, Sheree; Torzillo, Paul J; Buntain, Helen; Connor, Anne; Adsett, Don; et al.
Abstract : Introduction: Acute respiratory infections (ARIs) are leading causes of hospitalisation in Australian children and, if recurrent, are associated with increased risk of chronic pulmonary disorders later in life. Chronic (>4 weeks) cough in children following ARI is associated with decreased quality-of-life scores and increased health and societal economic costs. We will determine whether a validated evidence-based cough algorithm, initiated when chronic cough is first diagnosed after presentation with ARI, improves clinical outcomes in children compared with usual care. Methods and analysis: A multicentre, parallel group, open-label, randomised controlled trial, nested within a prospective cohort study in Southeast Queensland, Australia, is underway. 750 children aged <15 years will be enrolled and followed weekly for 8 weeks after presenting with an ARI with cough. 214 children from this cohort with persistent cough at day 28 will be randomised to either early initiation of a cough management algorithm or usual care (107 per group). Randomisation is stratified by reason for presentation, site and total cough duration at day 28 (<6 and ≥6 weeks). Demographic details, risk factors, clinical histories, examination findings, cost-of-illness data, an anterior nasal swab and parent and child exhaled carbon monoxide levels (when age appropriate) are collected at enrolment. Weekly contacts will collect cough status and cost-of-illness data. Additional nasal swabs are collected at days 28 and 56. The primary outcome is time-to-cough resolution. Secondary outcomes include direct and indirect costs of illness and the predictors of chronic cough postpresentation. Ethics and dissemination: The Children's Health Queensland (HREC/15/QRCH/15) and the Queensland University of Technology University (1500000132) Research Ethics Committees have approved the study. The study will inform best-practice management of cough in children. Trial registration number: ACTRN12615000132549.